Institutional and policy analysis of river basin management : the Guadalquivir River Basin, Spain - Bhat, Anjali (Policy research working paper, 2005)
"The authors describe and analyze river basin management in the Guadalquivir River Basin in Spain. The Guadalquivir river flows westerly across southern Spain, with nearly all of its 57,017 km2 drainage area within the region of Andalusia. Water management issues in this semi-arid, heavily agricultural, but rapidly urbanizing region include drought exposure, water allocation, water quality, and in some areas, groundwater overdraft. A river basin agency (Confederacion Hidrografica del Guadalquivir, or CH Guadalquivir) has existed within the basin since 1927, but its responsibilities have changed substantially over its history. For much of its life, CH Guadalquivir's mission was water supply augmentation through construction and operation of reservoirs, primarily to support irrigation, under central government direction with little provision for water user participation. Following the Spanish political system's transformation and Spain's accession to the European Union, water law and policy changes greatly expanded CH Guadalquivir's responsibilities and restructured it to incorporate representation of some basin stakeholders. Although the basin agency's accomplishments in reservoir construction have been prodigious, its record of performance with respect to its newer responsibilities has been mixed, as have perceptions of its openness and responsiveness to basin interests other than irrigators. This paper--a product of the Agriculture and Rural Development Department--is part of a larger effort in the department to approach water policy issues in an integrated way. The study was funded by the Bank's Research Support Budget under the research project "Integrated River Basin Management and the Principle of Managing Water Resources at the Lowest Appropriate Level: When and Why Does It (Not) Work in Practice?""--World Bank web site